Prince Yaroslav Vsevolodovich and the succession crisis of 1195 - Dimnik Martin (Сіверщина в історії України, 2014)
In 1195 the Monomashichi, Ryurik Rostislavich of Kiev, his brother David of Smolensk, and Vsevolod Bol’shoe Gnezdo of Suzdalia, demanded that Yaroslav Vsevolodovich and the Ol’govichi of Chernigov pledge never to seize from them or their descendants their patrimonies of Kiev and Smolensk. Yaroslav proclaimed bluntly that following Ryurik and David’s death succession to Kiev would be determined by God’s providence, that is, by military force. Significantly, in his negotiations with the Rostislavichi, Yaroslav was supported by Vsevolod Bol’shoe Gnezdo. У 1195 р. київський князь Рюрик Ростиславич, його брат смоленський князь Давид і суздальський князь Всеволод «Велике Гніздо» вимагали від чернігівських князів Ярослава Всеволодовича та Ольговичів обіцянки під клятвою ніколи не займати вотчин Мономашичів – Києва й Смоленська. Однак Ярослав зухвало відповів, що після смерті Рюрика і Давида володіння Києвом визначить Боже провидіння, тобто воєнна сила. Важливо, що у переговорах Ярослава з Ростиславичами його підтримав Всеволод «Велике Гніздо». В 1195 г. киевский князь Рюрик Ростиславич, его брат смоленский князь Давид и суздальский князь Всеволод «Большое Гнездо» потребовали от черниговских князей Ярослава Всеволодовича и Ольговичей клятвенного обещания никогда не занимать вотчин Мономашичей – Киева и Смоленска. Однако Ярослав дерзко ответил, что после смерти Рюрика и Давида владение Киевом определит Божье провидение, т. е. военная сила. Важно, что в переговорах Ярослава с Ростиславичами его поддержал Всеволод «Большое Гнездо».